Variables Associated with Endometriosis-related Pain: A Pilot Study using a Visual Analogue Scale - Mauro Cozzolino; Maria Elisabetta Coccia; Giacomo Lazzeri; Francesca Basile; Gianmarco Troiano
Abstract Objective Endometriosis is a complex disease, and pain is an important component of the syndrome. One of the most used methods to assess pain is the visual analogue scale (VAS). The aim of the present research was to study the pain experienced by patients who referred to our unit for endometriosis, using the VAS to understand the variables that could influence it. Methods We have conducted a prospective study from February 2012 to December 2016, enrolling 388 patients who referred to a university hospital, in Florence, Italy. We have included in the present study patients during their follow-up for endometriosis; we have also included patients who underwent surgery with a histological diagnosis of endometriosis. We have collected sociodemographic and clinical information regarding age, body mass index (BMI), smoking habit, number of pregnancies, and endometriosis staging. Finally, we have administered the VAS for several symptoms. Results Dysmenorrhea was the symptom associated with the highest perception of pain (mean VAS score of 5.76). The logistic regression showed that the stage of endometriosis could influence the pain associated to constipation and to dysuria. The linear regression showed that age couldinfluencethe pain associated to constipation, to dyspareunia,and to dysmenorrhea. A positive correlation was found between dysmenorrhea and chronic pelvic pain(CPP), between dysmenorrhea and dyspareunia, and between constipation and dysuria. Conclusion Using a validated method, the VAS, we have studied the pain experienced by a group of patients with a history of endometriosis and observed that smoking habit and BMI did not influence the VAS scores, and that dysmenorrhea was associated with the highest perception of pain.